GAMBARAN TINGKAT KEPUASAN PASIEN DALAM MENERIMA MANAJEMEN NYERI DI INSTALASI GAWAT DARURAT RSUD PASAR MINGGU - Nadhira Salma Syahdan, (2023)
Pain is the main reason patients visit the emergency department. A 2012 UK Survey found that 64% of the total respondents cited pain as a reason they entered the emergency department. Pain management success in the emergency department is an indicator of hospital services quality that impacts patient satisfaction. This study was conducted to determine description of the level of satisfaction of patients who received pain management in the emergency department of Pasar Minggu General Regional Hospital. Respondents were characterized by: age, gender, level of education, medical diagnoses received and medications. This study used descriptive quantitative research methods with a survey type of research with a study population of all patients who entered the emergency department of Pasar Minggu General Hospital with the main complaint of pain. The sampling technique was purposive sampling method. Data collection methods used questionnaires and medical records. Data analysis using univariate analysis. The results of the analysis of 63 respondents, the average respondent was 37 years old, female gender, high school education, had a medical diagnosis of gastrointestinal disorders and received ketorolac pharmacology therapy. The results showed that the majority of respondents as many as 28 people (44.4%) had a fairly satisfied level of satisfaction with the pain management received at the emergency department of Pasar Minggu General Hospital. Emergency department nurses are expected to be motivated to improve their ability to provide pain management as a nursing intervention and provide information to patients to use non-pharmacological pain management as a combination to relieve pain.